Islamic Community Development Study Program Strategy Towards Superior Accreditation (Swot Analysis of the PMI UIN Alauddin Makassar Study Program) - Haeruddin; Riyadi, Agus; Sahib, Muzdalipah; Wahyuni, Andi Indri (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2024)
This research aims to identify and map the Strengths, Weaknesses, Opportunities and Challenges of the Islamic Community Development Study Program at the Faculty of Da'wah and Communication at UIN Alauddin Makassar to become a superior accredited study program. This type of research is descriptive qualitative using a phenomenological approach. Data collection techniques through observation, interviews and documentation. The results of this research show that: 1) The strengths of the Islamic Community Development study program include the availability of formal governance and governance system documents, the availability of formal organizational structure documents, and the availability of valid evidence that includes credibility, transparency, accountability, responsibility and fairness. 2) The weaknesses of the Islamic Community Development study program are the lack of competent teaching staff, limited curriculum, limited facilities, lack of funding, and minimal collaboration with external parties. 3) Opportunities for the Islamic Community Development study program include developing a relevant and innovative curriculum, collaborating with leading institutions, using digital technology, training and competency development. 4) The challenges of the Islamic Community Development study program are limited human resources, limited funding, limited infrastructure and facilities, curriculum challenges, competition with other study programs, bureaucratic and regulatory obstacles, challenges in research and publication.